Comparison of Oral Versus Normal and High-Dose Rectal Paracetamol in the Treatment of Fever in Children - Bastola, Ramchandra; Shrestha, Shree Krishna; Bastola, Bhawana Sigdel; Shrestha, Dhurba; Sharma, Yograj (Journal of Nepal Paediatric Society, 2018)
Correction: On 13th June 2018 the author Yog Raj Sharma was changed to Yograj Sharma Introduction: Paracetamol is the most commonly used drug in paediatrics with the standard dose (15 mg/kg) of oral and rectal paracetamol preparations interchangeably is used to treat fever in children, assuming they have equal antipyretic effect. We did a study to compare the effectiveness of two different rectal doses of paracetamol: 15 mg/kg and 30 mg/kg to that of a standard oral dose of 15 mg/kg. Material and Methods: This is a prospective, interventional, randomized controlled study done in Western Regional Hospital, Nepal in which 192 children with fever aged six months to six years. Study duration was August 2015 to October 2015. The sample included 63 in the oral normal dose group (15mg/kg), 59 in normal dose rectal group (15mg/kg) and 70 in high dose (30mg/kg) rectal paracetamol group. Temperature was recorded before and after the administration of paracetamol at an interval of 30, 60, 120, and 180 minutes by using a digital thermometer. Results: Total of 59 patients received 15 mg/kg rectal Paracetamol (group A), 70 received 30 mg/kg rectal Paracetamol (group B), and 63 received 15 mg/kg oral Paracetamol (group C). Mean temperature before giving medication in Group A, B and C respectively were 101.7° F, 101.9° F and 101.5° F. At 30 min temperature was 100.8° F, 100.8° F and 100.66° F, while at 60 minutes temperature was 99.9° F, 99.7° F, and 99.7° F respectively for Group A,B and C. But at 120 and 180 minutes temperature decreased significantly who got rectal 30 mg/kg of paracetamol. Conclusions: Rectal paracetamol in a dose of 30mg/kg is more effective than oral paracetamol in a dose of 15 mg/kg. However oral paracetamol given in a dose of 15 mg/ kg is more effective than rectal paracetamol in a same dose.